A Configurable Interface for Analog Sensor Outputs - Faik Başkaya; Baran Demirer (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Reading out analog sensor outputs can be a challenging task at low frequencies because of the low frequency noise. To obtain a sensor signal clearly, special interface circuits are required. By using such circuits, analog signals are cleaned from offset, drift and 1/f noise. Besides, if the interface circuitry is configurable, it can be possible to interface to inputs at different frequency ranges. At the interface block, analog sensor output signal is moved to a frequency band where low frequency noise effects are not dominant by using chopping modulation technique. The frequency-shifted signal is then filtered using various filter types. To remove the low frequency noise before moving the signal back to the original band, Gm-C filter is used. The entire topology can be configured by a 5-bit digital to analog converter (DAC) called Biasing DAC (BDAC). This allows us to digitally change the biasing current of operational transconductance amplifiers (OTA), so that OTA based amplifiers and filters can operate at different frequency ranges. As conclusion, a configurable analog sensor interface has been designed. The design and layouts have been realized and simulated in Cadence Virtuoso using UMC 130nm CMOS technology.